Energy availability and density estimates in African ungulates - Pettorelli, Nathalie; Bro-Jørgensen, Jakob; Durant, Sarah M; Blackburn, Tim; Carbone, Chris (The American naturalist, 2009)
While many studies have investigated the link between primary productivity and species richness, the link between primary productivity and species abundance is still poorly understood. We explored how primary productivity, assessed by the satellite-based normalized difference vegetation index, influenced density estimates in 13 African ungulate species. We found that primary productivity generally correlated positively with density estimates. However, this link was more pronounced for some species than for others, and information regarding the area surveyed needed to be taken into account to highlight this functional relationship. Detailed consideration of measurements of productivity in broadscale studies identify a general link between primary productivity and abundance of African ungulates and highlight remote-sensing-based analyses as a potentially crucial tool in assessing the population consequences of future changes in primary productivity on this continent.